THE IMPACT OF POLITICAL EVENTS ON THE INDONESIA STOCK EXCHANGE - Amtiran, Paulina Yuritha (Universitas Nusa Cendana, 2025)
This study was conducted to determine the effect of events or political occurrences on the presidential and vice-presidential elections in Indonesia in 2019. This study employs an event study method, which examines an event in relation to the abnormal returns of property sector stocks on the market before and after the elections in 2019. This research was conducted seven days before and seven days after the election in 2019. The sampling technique was conducted using the purposive sampling method, yielding 20 samples. Analysis of the data in this study utilized the Shapiro-Wilk one-sample test for normality, and hypothesis testing employed the one-sample t-test and paired samples t-test. The results of the one-sample t-test and the paired sample t-test indicated that there were no abnormal stock returns during the period before and after the presidential and vice-presidential elections in 2019. Keywords: Abnormal Return; Average Abnormal Return; Election; Event Study; Political Events